2018
DOI: 10.1186/s12931-018-0727-x
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia promotes melanoma lung metastasis via oxidative stress and inflammation responses in a mouse model of obstructive sleep apnea

Abstract: BackgroundRecently, increased tumor incidence and cancer-related mortality have been reported among patients with obstructive sleep apnea (OSA). Intermittent hypoxia (IH), the hallmark feature of OSA, contributes to the metastasis of tumors. However, the molecular mechanisms by which tumor metastasis is accelerated by OSA-like IH remain to be elucidated.MethodsC57BL/6 J male mice were subjected to intravenous injection of B16F10 melanoma cells before receiving IH treatment. Then, the animals were randomly dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 55 publications
2
65
0
1
Order By: Relevance
“…Most cancer-related OSA studies employ the airtight box model to generate intermittent hypoxia independent of the other physiological effects associated with OSA. Several studies have been published in the last 5 years, mostly with melanoma and lung cancer models (5,7,9,51,85). These confirm an important role for systemic intermittent hypoxia in tumor growth and metastasis.…”
Section: Animal Models: Intermittent Hypoxia Increases Tumor Growth Amentioning
confidence: 77%
See 1 more Smart Citation
“…Most cancer-related OSA studies employ the airtight box model to generate intermittent hypoxia independent of the other physiological effects associated with OSA. Several studies have been published in the last 5 years, mostly with melanoma and lung cancer models (5,7,9,51,85). These confirm an important role for systemic intermittent hypoxia in tumor growth and metastasis.…”
Section: Animal Models: Intermittent Hypoxia Increases Tumor Growth Amentioning
confidence: 77%
“…Mouse models of intermittent hypoxia mimicking OSA show enhanced cancer growth, invasion, and metastasis (5,7,9,85). Intermittent hypoxia enhances both the early and late stages of metastasis, which was confirmed in a spontaneous and an induced metastasis model (subcutaneous or intravenous injection of melanoma cells, respectively) (7).…”
Section: Animal Models: Intermittent Hypoxia Increases Tumor Growth Amentioning
confidence: 80%
“…46,47,[84][85][86][87][88][89] These microenvironmental stress related changes in cancer cell metabolism are frequently associated with greater ROS production. 90 1.4 | Switch in redox control from de novo GSH synthesis to NADPH from the PPP in advanced cancer cells One major mechanism for enhancing ROS levels in cancer cells occurs via a feedback amplification loop involving ROS-mediated increase in cytosolic NADPH production. Thus, metabolic profiling 91,92 and other studies described below have shown for many cancer cell types that glycolysis is partly shunted via Glc6PDH into the oxidative PPP F I G U R E 2 The thioredoxin reductase (TrxR/Trx) system of thiol:oxidoreductases for redox regulation.…”
Section: Why the Mitochondrial Ros Production System Provides Novelmentioning
confidence: 99%
“…The tumor microenvironment during rapacious growth phases will concomitantly cause intermittent periods of hypoxia, acidosis, and nutrient deprivation resulting in hypoglycemia, all factors which consequently induce a major reprogramming of cancer cell metabolism . These microenvironmental stress related changes in cancer cell metabolism are frequently associated with greater ROS production …”
Section: Introductionmentioning
confidence: 98%
“…The processes are also under the influence of multiple triggers and pathways, and the clinical implications of activation of PD‐L1/PD‐1 axis need to be put into perspective. One interesting point in the story of OSA and cancer is that, among various malignancies, melanoma has been most consistently observed to be associated with OSA, especially in younger patients, and IH was shown to promote melanoma lung metastasis via oxidative stress and inflammation . Melanoma is also a tumour that is highly amenable to immunotherapy targeting the PD‐L1/PD‐1 axis …”
mentioning
confidence: 99%